MODERNISASI PRODUKSI GULA AREN DI DESA TONGO KECAMATAN SEKONGKANG KABUPATEN SUMBAWA BARAT - Saleh, Muhammad; Harjito (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
This study aims to formulate alternative strategies that must be appliedin the development of palm sugar production through modernization to increasethe quality and quantity of the product so that it has a direct impact on improvementwelfare of the village community, especially palm sugar craftsmen. Research sitesimplemented in Sejorong Hamlet, Tongo Village, Sekongkang District, DistrictWest Sumbawa. When the research was carried out in November 2019 andFebruary 2020. The type of research used in this study is a methoddirect survey. The data collected comes from primary data and datasecondary. Primary data is done by means of field observations, documentation andinterview with palm sugar crafter using a list of questions(Question). Secondary data were obtained from various related agencies andinformation from various literatures related to this research. PopulationIn this study, there are 4 traditional palm sugar craftsmenand the craftsmen of the Jalit L estari group of Tongo Village. The sample in this study was takenby means of purpose sampling, namely determining the sample with a specific goal. Techniquedata analysis using descriptive analysis to find out about modernizationpalm sugar production in Tongo Village and analysis of alternative strategies usingSWOT analysis is used to determine the development strategy. Resultresearch shows that based on internal and external analysis, small industryPalm sugar in Tongo Village, Sekongkang District has the power tomaintained or improved, and has opportunities that can be exploitedwell and as much as possible. The best development strategyused is a strategy that supports aggressive growth.